Assessing the effect of shift work among petrochemical Industries staff at Mahshahr, Iran - Kazemi, Maryam; Abadi, Alireza; Zayeri, Farid; Hassanzade, Hormoz (Archives of Advances in Biosciences, 2017)
This study aims to examine the effect of shift work on overweight and obesity, hypercholesterolemia and GHQ score (GHQ-28) as an indicator of psychological well-being in subjects working in petrochemical industry sited in Mahshahr, west of Iran. In This longitudinal study, population consisted of 2493 (1321 day workers and 1171 shift workers) whose mean ages were 46.18 years for day workers and 45.53 years for shift workers, during a four years period (from 2008 to 2011). All workers were investigated by Persian version of General Health Questionnaire-28 (GHQ-28) as screen tool. The serum cholesterol, height and weight were measured with definitions of hypercholesterolemia as serum total cholesterol 220 mg/dl, overweight and obesity as body mass index (BMI) 25 kg/m2 .A conditional joint random effects models approach was applied to explore the effect of shift working on multivariate responses over this period of time. Shift work was significantly associated with GHQ score and BMI. Results indicated that the shift workers had about 0.65 higher mean scores of GHQ than the day workers and 0.18 higher BMI (95% CI 0.17 to 1.14) and (95% CI 0.05 to 0.27), respectively. Shift work did not show significant relationship with hypercholesterolemia (95% CI -0.27 to 0.009). The results of the present study suggest that shift work may be directly responsible for increased body fatness and is associated with psychological problems.